Numerical and experimental studies on a novel Steinmetz treatment chamber for inactivation of Escherichia coli by radio frequency electric fields. (June 2017) - Masood, Hassan; Razaeimotlagh, Adel; Cullen, Patrick J.; Trujillo, Francisco J.
Abstract: Radio frequency electric field (RFEF) is an emerging non-thermal food processing technology that is alternative to pulsed electric fields (PEF). A novel Steinmetz treatment chamber design, that increases homogeneity of the electric field distribution, has been proposed and constructed. The design was performed and evaluated via Multiphysics modelling. The model was validated by comparison with experimental measurements of outlet temperature, power consumption and current. Inactivation studies showed the influence of electric field intensity, temperature, and treatment time on the inactivation of Escherichia coli in saline water with electrical conductivities between 0.02 and 0.1 S m − 1 . A maximum inactivation of 3.6 log CFU mL − 1 was obtained at 26.5 kV cm − 1, 45 °C and 900 μs treatment time. An energy demand of 63 kJ kg − 1 is required for 1 log reduction, when processing at 25 °C, for foods having 0.1 S m − 1 conductivity at 20 °C, but energy consumption increases with the electrical conductivity. Highlights: A novel treatment chamber design is proposed for radio frequency electric fields food processing. Nearly uniform distribution of electric field in treatment zone was obtained. Thermal hot spots are reduced by increasing flow rates due to residence time and turbulence. E. coli was inactivated at various process conditions, up to maximum 3.6 log CFU mL − 1 . 1 log CFU mL − 1 inactivation was obtained electrical conductivity as high as cranberry juice.